Surgical treatment in a bovine with vagal indigestion syndrome: case report - García B., Cristina (2019)
It is reported the case of a pregnant Holstein cow with abdominal distension, depression, decrease in milk production. In the clinical examination ruminal hypermotility was observed, both in the regional inspection and in the auscultation of the rumen. In the exploratory puncture in the left paralumbar fossa, bubbles were observed, confirming the presence of foamy tympanism in the rumen. The clinical signs showed a picture compatible with the vagal indigestion syndrome. An exploratory laparotomy was performed to confirm the diagnosis and evaluation of the damage of the organ, and as a therapeutic measure, a rumenotomy was conducted to remove most of the ruminal content. After the surgical intervention, the physiological constants were restored. The animal showed remarkable improvement and ended the pregnancy successfully.